Prevalence Of Hypothyroidism In Chronic Kidney Disease Among Sample Of Iraqi Patients. - Allawi, Ali A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Patients with chronic kidney disease have multiple alterations of thyroid hormone metabolism in the absence of concurrent thyroid disease. These may include elevated basal TSH values, which may transiently increase to greater than 10 mU/liter, blunted TSH response to TRH, diminished or absent TSH diurnal rhythm, altered TSH glycosylation, and impaired TSH and TRH clearance rates. In addition, serum total and free T3 and T4 values may be reduced, free rT3 levels are elevated while total values are normal, serum binding protein concentrations may be altered, and disease-specific inhibitors reduce serum T4 binding . Objective:. To assess the prevalence of hypothyroidism and u/s abnormalities of thyroid gland in patients with chronic kidney disease at different levels of estimated glomerular filtration rate (eGFR) and their association with age , sex and duration of chronic renal failure . cross sectional study. Patients and Method: a cross sectional study total of 50 patients who seek medical advice in Baghdad teaching hospital (29 male , 21 female) , the mean of their age was 60, with established chronic kidney disease were categorized into five groups according to the stages of chronic kidney disease . Full clinical, biochemical ( includes blood urea , serum creatinine , total T3, total T4 , TSH ) , thyroid ultrasonography studies were performed to all patients in this study. Risk factors such as hypertension, diabetes mellitus, smoking and family history of CKD were also recorded. Type of treatment of CKD whether conservative or renal replacement therapy (in form of peritoneal or hemodialysis) were also. Results:- From a total of 50 patients with chronic kidney disease (CKD ), eight patients had hypothyroidism (16 %) , three patients from stage 4 CKD and five patients from stage 5 CKD . Twelve patients from study sample had abnormalities in thyroid ultrasonography (24%) , one patient from stage 2 CKD , three patients from stage 3 CKD ,three patients from stage 4 CKD and five patients from stage 5 CKD . Thyroid ultrasound abnormalities includes six patients with simple goiter and six patients with multinodular goiter .From those eight patients with hypothyroidism , six patients were males (75%) and two patients were females (25%) .Regarding 12 patients with thyroid u/s abnormalities , five patients were male (41.6%) and seven patients were female (58.4%).Statistical analysis showed a significant association between drop in GFR and drop in thyroid function, from 13 patients in stage 4 CKD , three patients (23.07%) had hypothyroidism , and from 23 patients in stage 5 CKD , five patients (21.739%) had hypothyroidism . Conclusion:- reduced glomerular filtration rate was associated with an increased prevalence of hypothyroidism, with many subclinical cases. Future studies are needed to determine the potential adverse effects of subclinical and clinical hypothyroidism in persons with chronic kidney disease.